Taxonomic and nomenclatural notes on neotropical Commelina (Commelinaceae), and an identification key for Brazil, Guyana, Paraguay, Suriname and Uruguay - Hassemer, Gustavo (Phytotaxa, 2017)
Here, I present a taxonomic and nomenclatural revision of some names within the neotropical Commelina (Commelinaceae), especially those published by Moritz August Seubert in Flora brasiliensis: C. agraria var. repens, C. guyanensis, C. martiana, C. platyphylla, C. platyphylla var. balansae, C. pohliana, C. rufipes, C. schomburgkiana, C. schomburgkiana var. brasiliensis and C. vestita, in addition to Commelinopsis glabrata (basionym of Commelina rufipes var. glabrata). The complicated nomenclatural status of names invalidly published by Moritz Richard Schomburgk in 1849 in his Versuch einer Fauna und Flora von Britisch-Guiana is discussed. Furthermore, I provide an identification key to the nine species of Commelina that occur in Brazil, Guyana, Paraguay, Suriname and Uruguay.